Analisis model penanaman nilai toleransi untuk mengurangi kekerasan siswa sekolah dasar: studi kasus di kabupaten Sragen - Ahmad, Nurlita Avifani; Habiby, Wahdan Najib (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Violence against children tends to rise from year to year, with no exception to violence in school neighborhoods. The negative impact of violence on children varies, from short-term to long-term. Therefore, extra attention is needed from schools such as teaching tolerance to students. The study aims to look at and create learning models that can be used by primary schools in the cultivation of tolerant attitudes in children so that it is expected to reduce the rate of violence in children. This model of tolerance learning includes teaching tolerance in the classroom ranging from preparation, implementation, to evaluation, and is supported by the school curriculum. The research was carried out at Puro State SD 4 Sragen. The research uses a qualitative approach to case studies by conducting observations, interviews, lifts, and documentation. Research shows that by cultivating tolerance towards others and regularly adopting ethical behavior, children can change their attitudes for the better so that violence can be reduced. Therefore, this model of cultivating tolerance values is designed to serve as a benchmark for a primary school in applying tolerance teaching and good habits to children.